Childlessness and Disability. An Intersectional Analysis on Access to Motherhood for Women with Disabilities in Italy - Micalizzi, Ester (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
The aim of this contribution is to explore, through the feminist perspective on disability (Thomas, 1997; Wendell, 1996; Garland-Thomson, 2004; Morris, 1991; 2004), the way in which disabled women reflect and narrate about (not) becoming mothers and the mechanisms of ’maintaining’ childlessness. For this purpose, 18 biographical-narrative interviews were conducted in the period between May 2020 and September 2021 with a group of women with visible/invisible motor disabilities, both mothers and non-mothers, and aged between 20-50 years living in the city of Turin. The contribution is part of a PhD project on reproductive trajectories and narratives of embodied motherhood in dis-abled bodies. While the issue of parenthood for disabled people has begun to be investigated in international social research in recent years (Malacrida, 2009; Frederick, 2017), the processes of constructing meanings related to childlessness have not, until now, been the subject of in-depth research interest. By looking at the tensions between their biographical positioning, social norms about who (and if) should become a parent, and the embedded effects of disability (Thomas, 1997), it is possible to demonstrate how their childlessness status challenges the prevailing common-sense perception that views the experience of childlessness as an obvious and natural state characterised by lack of agency (Thomas, 1997). On the other hand, the variability of these different ’childless biographies’ allows us to understand the social mechanisms of childlessness maintenance behind the state of childlessness, such as stigma, misrecognition, silence and desexualisation and socialisation to gender roles. These findings are relevant as they allow not only to move beyond a mainstream approach on childlessness, but to detect the intersectionality of struggles between Reproductive Justice (Ross and Salinger, 2017) and the Independent Living Movement (Morris, 2004).